Adhesive-based tendon-to-bone repair: failure modelling and materials selection. Issue 153 (10th April 2019) - Avgoulas, Evangelos I.; Sutcliffe, Michael P. F.; Linderman, Stephen W.; Birman, Victor; Thomopoulos, Stavros; Genin, Guy M.
Abstract : Surgical reattachment of tendon to bone is a procedure marked by high failure rates. For example, nearly all rotator cuff repairs performed on elderly patients with massive tears ultimately result in recurrence of tearing. These high failure rates have been attributed to stress concentrations that arise due to the mechanical mismatch between tendon and bone. Although recent studies have identified potential adhesives with mechanical properties tuned to alleviate these stress concentrations, and thereby delay the onset of failure, resistance to the progression of failure has not been studied. Here, we refined the space of adhesive material properties that can improve surgical attachment by considering the fracture process. Using cohesive zone modelling and physiologically relevant values of mode I and mode II adhesive fracture toughnesses, we predicted the maximum displacement and strength at failure of idealized, adhesively bonded tendon-to-bone repairs. Repair failure occurred due to excessive relative displacement of the tendon and bone tissues for strong and compliant adhesives. The failure mechanism shifted to rupture of the entire repair for stiffer adhesives below a critical shear strength. Results identified a narrow range of materials on an Ashby chart that are suitable for adhesive repair of tendon to bone, including a range of elastomers and porous solids.